Digital Javanese Script Literacy for Cultural Tourism Communication - Yenni Sri Utami; Ida Wiendijarti; Oliver Samuel Simanjuntak (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Bantul Regency promotes cultural tourism through the "Bantul Bumi Mataram" branding, which positions Mataram heritage, including the Javanese script (Hanacaraka), as a core destination asset. However, most tourism actors in Bantul have limited literacy in Javanese script, restricting their ability to explain cultural symbols to visitors and reducing the effectiveness of this branding strategy. Objective: This study develops and evaluates an Android-based digital literacy model for Javanese script that improves tourism actors’ script literacy and strengthens cultural tourism promotion in Bantul Regency. Methods: This research and development (R&D) study combined a needs analysis with a prototyping approach, using interviews, observation, and questionnaires administered to a purposive sample of tourism actors [author to confirm exact sample size] in Bantul Regency. The application was built with Adobe Flash Professional CS6 and evaluated through limited user trials with pre-test/post-test measurement of script-reading accuracy [author to confirm test scores]. Results: Tourism actors initially recognized only basic Hanacaraka characters and could not read simple sentences. After using the application, participants showed improved script-reading accuracy in the post-test [author to insert percentage/effect size] and reported greater confidence in explaining Javanese cultural symbols to visitors. Conclusion: The Android-based digital literacy model strengthens tourism actors’ Javanese script competence and reinforces Bantul’s cultural identity within the Bantul Bumi Mataram branding strategy, offering a replicable approach for digitally preserving other endangered scripts.